SYNTHESIS OF METAL-ORGANIC (COMPLEXES) COMPOUNDS COPPER(II)-IMIDAZOLE FOR ANTIVIRAL HIV CANDIDATE - Sucipto, Teguh Hari; Martak, Fahimah (Institute of Topical Disease, 2015)
The human immunodeficiency virus (HIV) is viruses known as rotaviruses. Potential target for therapeutic is reverse transcriptase (RT), possesses an RNA-dependent DNA polymerase, DNA-dependent DNA polymerase and ribonuclease H fuctions. Imidazoles have high anti-HIV inhibitory activity, some derivates of imidazole reported drugs. 8-chloro-2,3-dihydroimidazole[1,2-b][1,4,2]benzodithiazine-5,5-dioxides and 9-chloro-2,3,4-trihydropyri-mido[1,2-b][1,4,2]benzodithi-azine-6,6-dioxides. This compounds succesfully identified anti-HIV activity. Copper is a bio-essential element and copper complexes have been extensively utilized in metal mediated DNA cleavage for the generation of activated oxygen species. It has been reported that teraaza macrocyclic copper coordination compounds have anti-HIV activities. Studies have shown that these macrocyclic complexes can react with DNA in different binding fashions and exhibit effective nuclease activities. Complex compounds are compounds in which there is an atom that acts as the central atom and trotter group of molecules that can be either neutral or charged ions. Application a metal-organic (complex) compounds, especially copper metal and derivates of imidazole. So, in this study can explore new anti-HIV candidate.